(untitled) (The Pakistan Development Review, 1995)
The Eighth Five-Year Plan has allocated Rs 9.1 billion to the Population Welfare Programme (PWP) which constitutes 0.5 percent of the total plan size of Rs 1700.5 biIlion (in 1992-93). During 1992-93, a total of Rs 828.9 miIlion was allocated to PWP, of which 85 percent was reported to be utilised, which amounts to Rs 702.87 million. Service delivery of family planning is a major focus and component of the PWP. The major service delivery sources include Family Welfare Centres (FWCs) in both the government and NGO sectors, Mobile Service Units (MSUs), Reproductive Health Services (RHS), Village-based Family Planning Workers (VBFPW), Hakeems, and Private Medical Practitioners, etc. All sources of delivery of family planning during the three decades of programme efforts have achieved the maximum extent of effective coverage, estimated to be between 15-20 percent in early 1990s but no more than 5 percent to rural population [Rukanuddin and Hardee Cleveland (1992)]. Besides limited coverage, the low level of accessibility and limited contraceptive availability, particularly to rural populace, have also seriously affected the performance of the PWP. These concerns have been addressed in the Eighth Five-Year Plan, which aims at increasing the urban coverage from 54 percent to 100 percent and the rural coverage from 5 percent to 70 percent. The major mode of service delivery to increase the rural coverage is the ViII age-based Family Planning Worker (VBFPW) scheme that would offer FP services to approximately 12000 villages. This scheme, however, focuses on non-clinical and temporary methods only.